HUBUNGAN ANTARA RIWAYAT HIPERTENSI DENGAN KEJADIAN PREEKLAMSIA PADA IBU BERSALIN DI RSUD PROF. Dr. MARGONO SOEKARDJO PURWOKERTO - Ema Wahyuningrum; Nurhoeriyah - (Universitas Harapan Bangsa Purwokerto, 2015)
Maternal mortality rate in Indonesia is still high and is a major concern for health development in Indonesia. Preeclampsia is a cause of maternal and perinatalmortality is high, especially in developing countries like Indonesia. Past medicalhistory is a factor of preeclampsia. Existing conditions can include diabetes mellitus,heart disease and hypertension. Hospital Prof. Dr. Margono Soekarjo is the biggestreferral hospital in Banyumas regency, the data obtained the incidence ofpreeclampsia in the year 2011 as many as 374 cases (16.12%), in 2012 as many as551 cases (16.59%) and increased in the year 2013 as many as 555 cases (16.46%).The aim of research to determine the relationship between a history of hypertensionwith preeclampsia in women giving birth in hospitals Prof. Dr. Margono SoekarjoPurwokerto. This research is descriptive correlation with retrospective approach, thepopulation of all women giving birth in hospitals Prof.Dr.Margono SoekarjoPurwokerto as many as 3371 women giving birth, the sampling technique ispurposive sampling with 97 women who develop preeclampsia. The type of datausing secondary data and instrument used master tables as well as data analysisusing Chi-square. The result showed the majority of respondents do not have ahistory of hypertension as much as 54 respondents (55.7%), mostly experiencedpreeclampsia of 50 respondents (51.5%). There is a relationship between a history ofhypertensive disease with an incidence of preeclampsia in maternal (Ã¾-value (0.005)<Î± (0.05). There is a relationship between a history of hypertension withpreeclampsia Keywords: history of hypertension, preeclampsia, Mother Maternity